Inequality in democracy: Insights from an empirical analysis of political dynasties in the 15th Philippine Congress - Beja, Edsel L, Jr (Archīum Ateneo, 2012)
This paper presents metrics to estimate the size of political dynasties in the 15th Congress of the Republic of the Philippines and analyze the relationship between political dynasty and socio-economic outcomes. Results show that political dynasties comprise 70 percent of jurisdiction-based legislators in the current Congress. They possess higher net worth and win elections by larger margins of victory compared to not political dynasties. Jurisdictions of political dynasties are characterized by lower standards of living, lower human development, and higher levels of deprivation and inequality.